Respiratory sounds as a source of information in asthma diagnosis - Skalický, David; Lopot, František; Koucký, Václav; Kubový, Petr; Pohunek, Petr; Zoul, Václav; Jelen, Karel; Dynybyl, Vojtěch (Lékař a technika, 2017)
Around 300 million people all over the world at all age level suffer from asthma [1]. Patients with this disease have primarily difficult breathing with wheezing in respiratory sounds, cough and feeling of constricted chest. Therefore their physical activity is strongly limited [2]. Nowadays, there are several methods for asthma diagnosis, for example spirometry, measuring of peaks of expiratory velocity or measuring of bronchial reactivity. Although these methods are sufficiently reliable in most cases, they have also some imperfections, which are obvious especially by diagnosing of badly collaborating patients, e.g. small children aged up to three years. These infants can’t provide operations required for diagnosis, so results performed diagnosis are not reliable. For this reason, there is an idea of developing non invasive method of asthma diagnosis and other pulmonary diseases that would not need collaboration of patient [3]. One of the most probably working usable principles is comparison of air flow in airways of healthy and ill person. The difference of the air flow is caused by bronchial obstruction and constriction of airways of patient. There are other sounds and wheezing in the respiratory sounds detectable during breathing as a typical manifestation of the disease [4]. These phenomena can be detected by hearing of sound or by harmonic analysis.
Keywords: Respiratory Sounds; Fourierova analýza; Software; Humans; bronchiální astma; Asthma; mužské pohlaví; software; počítačové zpracování signálu; Respiratory Mechanics; Adolescent; Signal Processing, Computer-Assisted; lidé; mladiství; Fourier Analysis; dítě; Child; mechanika dýchání; respirační zvuky; Male